GERAKAN KELUARGA SEHAT CIPTAKAN GENERASI BERKUALITAS DAN BEBAS DARI DIABETES MELITUS DI DESA KERTOSARI KEC. PURWOSARI KAB. PASURUAN - budiono, budiono; Herawati, Tutik; Nataliswati, Tri; Pujiastuti, Nurul (Politeknik Kesehatan Kemenkes malang, 2025)
Diabetes mellitus (DM) is a health problem that continues to increase, especially in Indonesia. Health education is one of the main strategies in increasing public understanding of the dangers of DM, the importance of early detection, and the implementation of a healthy lifestyle. This community service uses education, demonstration and observation to evaluate the effectiveness of education and training on the level of knowledge and behavior of participants. A total of 30 participants participated in counseling and training on DM, healthy eating patterns, and physical activity. Measurements were taken before and after the intervention. The results of the community service Education increased participants' knowledge about the dangers of DM (50% to 85%), early detection (40% to 80%), and healthy lifestyles (45% to 90%). The training also increased understanding of choosing healthy food ingredients (55% to 85%) and processing low-sugar foods (50% to 80%). Participation in diabetic foot exercises increased by 20%, and other physical activities increased by 46.7%. Blood sugar checks showed that 66.7% of participants were in the prediabetes category. Education and training have been proven effective in improving knowledge and practice of diabetes prevention. Sustainable interventions are needed to reduce prediabetes rates and prevent the development of DM in the community.